2013
DOI: 10.1111/j.1423-0410.2012.01663.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics applied to transfusion plasma: the beginning of the story

Abstract: 'Safe blood' is and has always been the major concern in transfusion medicine. Plasma can undergo virus inactivation treatments based on physicochemical, photochemical or thermal methodologies for pathogen inactivation. The validation of these treatments is essentially based on clottability assays and clotting factors' titration; however, their impact on plasma proteins at the molecular level has not yet been evaluated. Proteomics appears as particularly adapted to identify, to localize and, consequently, to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 183 publications
(200 reference statements)
0
2
0
Order By: Relevance
“…Such functional alterations potentially determine the development and prognosis of a disease [41]. For this reason, recent analysis has revealed that over 95% of all currently known drug targets are proteins, covering about 93% of known drugtarget interactions [42]. To fully understand the essence and dynamic state of life's complexity, it is necessary to define the role of proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such functional alterations potentially determine the development and prognosis of a disease [41]. For this reason, recent analysis has revealed that over 95% of all currently known drug targets are proteins, covering about 93% of known drugtarget interactions [42]. To fully understand the essence and dynamic state of life's complexity, it is necessary to define the role of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that proteins, the direct actuators of vital biological functions, undergo changes in expression, posttranslational modifications (PTMs), and protein sequence variation during their lifetimes which control their functional activity that cannot be predicted from their genetic sequences. Such functional alterations potentially determine the development and prognosis of a disease [41]. For this reason, recent analysis has revealed that over 95% of all currently known drug targets are proteins, covering about 93% of known drug‐target interactions [42].…”
Section: Introductionmentioning
confidence: 99%